Personal and Animal Names in Japanese and Russian Texts Translated from a Fantasy Novel (Journal of Oriental Studies, 2022)
This paper analyzed a Russian translation text and the Japanese translation text of Harry Potter and the Philosopher’s Stone from the viewpoint of Descriptive Translation Studies proposed by Toury (1995). First, the present researchers situated the texts within the target culture systems, looking at their acceptability. The results revealed that although Japanese and Russian famous bookstore companies categorized the translated books as children’s literature, the Japanese version’s translator did not choose a certain readership and the Russian version’s translator and publishing company categorized it as роман, namely novel. In the Russian-speaking world, not children but adolescence people and adults usually read роман. Second, the present authors surveyed translation features of personal and animal names in the Japanese and Russian translation versions of Harry Potter and the Philosopher’s stone. Based on the seven translation procedures that Davies (2003) proposed (i.e., Preservation, Addition, Globalization, Omission, Localization, Transformation, and Creation), the present researchers classified the names and counted the number of each of the translation procedures. The results showed that Preservation was most frequently used in both the Japanese and Russian texts. In the Japanese translation version, the percentage of Preservation was about 80%. In the Russian translation version, the percentage of Preservation was about 50% and the percentage of Localization was about 30%. The Russian translator used Preservation and Localization frequently. According to Jaleniauskienė and Čičelytė (2009), Preservation was the procedure that emphasized the Source language and Localization was the procedure that emphasized the Target language. These results showed that the Russian translation version put more emphasis on the Target language than the Japanese translation version.